Trouble in Tiger country: isolated traumatic pancreatic transection – a case report - Ahmed Faidh Ramzee (17945120) (2023)
Isolated pancreatic transection is a rare surgical condition that occurs more commonly following blunt abdominal trauma. It carries a high degree of morbidity and mortality, and the management remains a source of debate as universally accepted guidelines are not well established owing to the paucity in clinical experience and large series. We presented a case of an isolated pancreatic transection following blunt abdominal trauma. The surgical management of pancreatic transection has evolved over the decades from aggressive approaches to more conservative measures. Given the lack of large series and clinical experience, no universal consensus exists, except for applying damage control surgery and resuscitation principles in critically unstable patients. For transections of the main pancreatic duct, most recommend excision of the distal pancreas. Concerns over the iatrogenic complications of wide excisions, particularly diabetes mellitus, have led to reconsideration and more conservative approaches, but it may fail in some cases. Other Information Published in: Journal of Surgical Case Reports License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/jscr/rjad071